2014
DOI: 10.1097/sap.0b013e318260555b
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of a Functional Gliding Surface With Extensor Retinaculum in Extensor Tendon Reconstruction in the Digits

Abstract: Extensor retinaculum grafting to replace lost periosteum is a technique that is easily used, uses locally available autogenous tissues, and produces excellent tendon function. Additionally, the histologic similarities between extensor retinaculum and periosteum add scientific merit to this novel approach. On the basis of our experience, we recommend the use of extensor retinaculum for periosteal reconstruction to provide an adequate gliding surface for a reconstructed tendon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 18 publications
0
5
0
1
Order By: Relevance
“…And up to now, these products have only been used to prevent adhesions of flexor tendons at the wrist or finger [16][17][18]. Other authors [19] have reported using autologous tissue like the extensor retinaculum at the wrist to prevent bone adhesions, but secondary donor site morbidity occurred. Although autologous tissue has been used to reconstruct the periosteum, there is no mention of it being used to prevent adhesions with 1.5 or 2.0 mm dorsal plates.…”
Section: Discussionmentioning
confidence: 96%
“…And up to now, these products have only been used to prevent adhesions of flexor tendons at the wrist or finger [16][17][18]. Other authors [19] have reported using autologous tissue like the extensor retinaculum at the wrist to prevent bone adhesions, but secondary donor site morbidity occurred. Although autologous tissue has been used to reconstruct the periosteum, there is no mention of it being used to prevent adhesions with 1.5 or 2.0 mm dorsal plates.…”
Section: Discussionmentioning
confidence: 96%
“…This anatomic entity thus seems perfectly suited for EDT protection. Barr et al likewise recommend the same flap to restore peritendinous glide in post-traumatic reconstruction [12].…”
Section: Discussionmentioning
confidence: 98%
“…27 Up to now, these products have only been used to prevent adhesions of flexor tendons at the wrist or finger. 28,29 Other authors 30 have reported using autologous tissue like the extensor retinaculum at the wrist to prevent bone adhesions, however, with associated secondary donor site morbidity. Although autologous tissue has been used to reconstruct the periosteum, there is no mention of it being used to prevent adhesions with 1.5 mm or 2.0 mm dorsal plates.…”
Section: Discussionmentioning
confidence: 99%